Intraplate uplift: new constraints on the Hoggar dome from the Illizi basin (Algeria). (25th February 2016) - English, Kara L.; Redfern, Jonathan; Bertotti, Giovanni; English, Joseph M.; Yahia Cherif, Rachida
Abstract: Zones of anomalously high topography within continental interiors, distant from active plate boundaries, are interpreted as being either dynamically supported by viscous flow in the underlying mantle or influenced by plate tectonics. Constraining the models of their genesis requires accurate data on the timing and dimensions of such features. New apatite fission‐track and thermal maturity data from the Illizi Basin in Algeria quantify the magnitude and timing of kilometre–scale uplift and exhumation of the northern flank of the Hoggar swell in North Africa. The findings of this study, integrated with previously published thermochronological data, confirm that long‐wavelength regional uplift occurred during the Cenozoic extending over a distance in excess of 1500 km from north to south. The uplift, centred on the Hoggar Massif, significantly impacted the flanking Illizi and Tim Mersoï basins. The combination of thermal history modelling and regional stratigraphic observations indicates that the onset of exhumation of the Illizi Basin likely occurred during the Eocene, broadly coincident with magmatism on the Hoggar Massif to the south and the onset of tectonic shortening in the Atlasic belt to the north.